2013
DOI: 10.1371/journal.pone.0047434
|View full text |Cite
|
Sign up to set email alerts
|

Neem Leaf Glycoprotein Activates CD8+ T Cells to Promote Therapeutic Anti-Tumor Immunity Inhibiting the Growth of Mouse Sarcoma

Abstract: In spite of sufficient data on Neem Leaf Glycoprotein (NLGP) as a prophylactic vaccine, little knowledge currently exists to support the use of NLGP as a therapeutic vaccine. Treatment of mice bearing established sarcomas with NLGP (25 µg/mice/week subcutaneously for 4 weeks) resulted in tumor regression or dormancy (Tumor free/Regressor, 13/24 (NLGP), 4/24 (PBS)). Evaluation of CD8+ T cell status in blood, spleen, TDLN, VDLN and tumor revealed increase in cellular number. Elevated expression of CD69, CD44 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…Neem leaf preparation was then extensively dialyzed against PBS and concentrated. Glycoprotein present in this preparation (NLGP) was isolated and characterized by the method described before [18,26]. The NLGP (25 g/100 l/mice) was injected to the mice using the insulin syringe (needle size: 0.30 mm to 8 mm).…”
Section: Neem Leaf Glycoprotein (Nlgp)mentioning
confidence: 99%
See 3 more Smart Citations
“…Neem leaf preparation was then extensively dialyzed against PBS and concentrated. Glycoprotein present in this preparation (NLGP) was isolated and characterized by the method described before [18,26]. The NLGP (25 g/100 l/mice) was injected to the mice using the insulin syringe (needle size: 0.30 mm to 8 mm).…”
Section: Neem Leaf Glycoprotein (Nlgp)mentioning
confidence: 99%
“…T cell surface phenotypic markers were assessed flow cytometrically after labeling of cells (1 × 10 6 ) with anti-mouse fluorescence labeled antibodies (CD4, CD8, CD44, CD69, KLRG1, CD28, and CD40) as described before [18,19]. Similarly, intracellular molecules (IFN␥, Granzyme B, Runx3, and pStat5) were stained with similar antibodies using cytofix-cytoperm reagents as discussed earlier [19,21].…”
Section: Flow Cytometric Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…This NLGP-generated anti-CEA immune response would be effective as a vaccine to lyse CEA(+) tumours in vitro and in vivo. Recent studies by Mallick et al ( 2013a ) found that treatment of mice bearing established sarcomas with neem leaf glycoprotein (NLP) (25 μg/mice/week subcutaneously for 4 weeks) resulted in tumour regression or dormancy. NLGP promoted the therapeutic antitumour immunity in mice by dynamically modulating the activation, expansion and recruitment of CD8(+) T cells into established tumours to induce signifi cant tumour cell lysis and inhibit growth of mouse sarcoma.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%